Thermal performance comparative analysis of nanofluid flows at an oblique stagnation point considering Xue model: a solar application. Issue 1 (2nd February 2022) - Ramzan, Muhammad; Shahmir, Nazia; Alotaibi, Hammad; Ghazwani, Hassan Ali S; Muhammad, Taseer
Abstract: This exploration aims to study the comparison of heat transfer capabilities of two nanofluid oblique, steady stagnation-point flow combinations comprising single-walled carbon/water (SWCNHs/water) and multiwalled carbon nanotube/water (MWCNTs/water) toward a stretching surface influenced by nonlinear thermal radiation employing the Xue model. This envisaged comparison model is inimitable and still scarce in the literature. Relying on the Tiwari–Das nanofluid model, a mathematical framework is constructed. The system of partial differential equations is converted using suitable transformations into an ordinary differential system of three equations, which is evaluated numerically using the bvp4c method. The physical behavior of significant parameters and their graphical representation are thoroughly examined. The results show that the SWCNHs/water nanofluid outperforms the MWCNTs/water nanofluid. It is further witnessed that SWCNH nanoparticle contained nanofluid has considerably greater thermal radiation than MWCNT nanoparticles. The envisaged model is also validated by comparing it with a published study. Graphical Abstract: